2016
DOI: 10.3168/jds.2016-11566
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of cooling dry cows across the United States

Abstract: Heat stress during the dry period reduces milk yield in the subsequent lactation of dairy cows. Our objectives were to quantify the economic losses due to heat stress if dry cows are not cooled and to evaluate the economic feasibility of dry cow cooling. We used weather data from the National Oceanic and Atmospheric Administration to calculate the number of heat stress days for each of the 50 US states. A heat stress day was declared when the daily average temperature-humidity index was ≥68. The number of dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 28 publications
2
64
0
1
Order By: Relevance
“…The total cost per stall for all systems ranged from $2,460 to $3,180 per stall. These costs fall within the estimates made by Kammel (2015) and are similar to the economic evaluation by Ferreira et al (2016), which assumed that the barn costs were $2,500 per stall when not including electrical components.…”
Section: Capital Costssupporting
confidence: 85%
See 1 more Smart Citation
“…The total cost per stall for all systems ranged from $2,460 to $3,180 per stall. These costs fall within the estimates made by Kammel (2015) and are similar to the economic evaluation by Ferreira et al (2016), which assumed that the barn costs were $2,500 per stall when not including electrical components.…”
Section: Capital Costssupporting
confidence: 85%
“…A 30% decrease in efficiency would reduce the design ventilation rate for the 8CRO system from 53 ACH to 37 ACH. The model did not estimate the cost of maintaining each type of fan; however, Ferreira et al (2016) suggested that maintenance would cost $15 per fan per year. Using this estimate, the mean, minimum, and maximum maintenance cost from all systems and stochastic observations (n = 109) was $0.90, $0.40, and $2.20 per stall per year, respectively.…”
Section: Operating Costs: Stochastic Modulementioning
confidence: 99%
“…Heat stress causes great economic loss to the livestock industry worldwide, particularly the dairy industry [1]. Increasing evidence suggests that heat stress not only affects the physiology, feed intake, and milk production but also the reproduction efficiency of dairy cattle [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Livestock, especially cattle, are expected to be directly impacted by climate change and increased heat stress but also indirectly though impacts on forage and feed grain yield reductions [33]. In the US, direct livestock losses due to heat stress are estimated to be $2.4 billion annually from decreased reproduction rates, feed consumption, and feed efficiency affecting animal growth rates [34][35][36][37]. Lower forage and feed quality are also expected [38] as increased temperatures negatively affect growth conditions and nutrient availability [39].…”
Section: Agricultural Studiesmentioning
confidence: 99%
“…[ [23][24][25][26][27][28] Texas: warmer and drier climate-reduced crop yields and increased losses due to extreme weather events [29,30] Texas: lower soil moisture leading to increased aquifer pumping and water stress [31] Texas: increased frequency of pest, disease, and invasive species which raises crop management costs [28,32] Livestock Increased heat stress and reduced forage and feed growth [33] Livestock losses from decreased reproduction rates, feed consumption, and feed efficiency affecting animal growth rates [34][35][36][37] Lower forage and feed quality due to increased temperatures affecting growth and nutrient availability [38,39] Texas: lower stocking rates and reduced per animal production due to warmer and drier conditions [33] Texas: increased supplemental feeding due to lower grassland growth rates, quality, and acreage with the expansion of woody plants [40] Texas: decreased animal productivity due to the expansion and greater incidence of disease, ectoparasites, and other pests [30,40,41] Supply Chain…”
Section: Climate Impacts On Agriculture Citationsmentioning
confidence: 99%